Implementation and challenges of project-based learning of STEAM in the university during the pandemic: A systematic literature review - Ellyzabeth Sukmawati; Norif Didik Nur Imanah; Dahlia Arief Rantauni (JINoP (Jurnal Inovasi Pembelajaran), 2023)
To achieve the intended educational outcome, a learning model that puts a focus on student-centered learning must be is implemented. According to investigations of university education, lecturers still dominate the learning process, and students' critical thinking skills are still insufficient. Using STEAM in Project-Based Learning (PjBL) is one method for fostering 21st-century skills. STEAM is an acronym for science, technology, engineering, art, and mathematics. STEAM is a term that was coined after incorporating art into the STEAM teaching component. This research aims to examine the implementation and challenges of Project-Based Learning of STEAM at the university during the pandemic. This research employs literature review as its method. Furthermore, within the method it uses several national and international publications that contain theoretical or verifiable information. An organized and comprehensive examination of the publications is discussed in order to investigate the impact of STEAM-integrated project-based learning on the development of 21st-century qualifications. The results showed that the implementation of STEAM-integrated Project-Based Learning fosters students' development of 21st-century skills. STEAM-integrated PjBL allows students a hands-on learning chance to apply the topics they have studied in a project activity by fusing many domains of study. Through the learning activities, students can put their communication, scientific literacy, critical thinking, creative thinking, and scientific process abilities into practice